The Semantics of “Grayness” in the Language of Polish Youth in Vilnius - Ušinskienė, Viktorija (Slavistica Vilnensis, 2023)
The article aims to reveal the concept of GRAY in the sociolect of Polish youth in Vilnius. The semantic analysis of the gray name szary is carried out against the background of the standard Polish language. The main task is to show what meanings accompany the name of this color in the respondents’ questionnaires and how they connote the world of non-linguistic reality. The conducted research shows that the respondents’ answers partially do not coincide with the definitions and connotations presented in the subject literature. For example, the prototypical associations with ash typical of Polish dictionaries did not appear in the questionnaires. However, in both varieties of the Polish language, the color gray is associated with natural phenomena (evening, clouds, rainy weather) and animals (mouse, hare, wolf, elephant, etc.). Differences are noticeable when it comes to the emotional component of the semantics of grayness: both negative (sadness, depression, failure, etc.) and positive (calmness, elegance, high class) connotations of the word szary ‘gray’ are characteristic of the youth sociolect, which emphasizes the greater ambivalence of the semantics of this term, compared to the situation in standard Polish.